Thresholds of transformation: UNRISD sustainable development performance Indicators pilot testing - Synthesis report - Bill Baue; Ralph A. Thurm (United Nations Research Institute for Social Development (UNRISD), 2022)
This report summarizes and synthesizes the outcomes of a pilot testing project on a set of UNRISD-designed Sustainable Development Performance Indicators (SDPI) that are intended to gauge whether economic entities are on a pathway consistent with the transformative goals and vision of the 2030 Agenda for Sustainable Development. The SDPIs transcend existing indicators by assessing actual sustainability impacts against normative, context-based thresholds and transformative change potential. Participants in the pilot project included enterprises and organizations in the for-profit enterprise (FPE) and social and solidarity economy (SSE) sectors, as well as sustainability standard setters and framework providers such as the World Bank, World Benchmarking Alliance, and Impact Management Project. The findings and analysis of the project hold significant implications on two levels: (i) implementability (the extent to which the full suite of indicators can be implemented); and (ii) transformativity (the extent to which the indicators- and the performance measurement, management and reporting they entail-can serve as levers for more significant and necessary systems change). The pilot testing showed that implementing indicators that assess sustainability performance relative to context-based thresholds and transformative potential is both feasible and desired by economic entities, standard setters and framework providers.
Keywords: 330; Sustainable Development Goals; Wirtschaftsindikator; Umweltbewertung; Sozialer Indikator; Nachhaltige Entwicklung; Systemtransformation; Welt